Pengaruh Kemampuan Teknik Personal, Program Pelatihan dan Pendidikan, Insentif, dan Partisipasi Manajemen Pada Kinerja Penerapan SIA - Irma Diana Putri, Ni Wayan; Dharmadiaksa, Ida Bagus (E-Jurnal Akuntansi, 2015)
Personal technical capabilities, training and education programs, the provision of incentives to employees, as well as the participation of management is very related to the performance of the application of accounting information systems. This research was conducted at Hotel Star Three, Four, and Five in Denpasar. This study used a sample of 85 employees using purposive sampling method. Used multiple linear regression analysis technique as a method of data analysis. Thus the results showed four independent variables are positive and significant effect on the performance of the application of accounting information systems.
Keywords: Application; Accounting Information Systems